Paying the piper eaudiobook Elizabeth macpherson series, book 4. - McCrumb, Sharyn (Elizabeth MacPherson, 1993)
Elizabeth has a plan for how she and her boyfriend Cameron can spend the summer together in Scotland. While Cameron researches the migratory patterns of seals, Elizabeth will join an archaeological dig on the nearby island of Banrigh. But Elizabeth's plans don't include a devastating plague which starts killing off her fellow crew members.